A Payoff of Cooperation and Non-cooperation: An Analysis of Pak-Afghan Relations during Cold War - Muhammad, Imraz (Journal of Peace, Development and Communication, 2021)
Pak-Afghan relations are consisting of non-cooperation and mistrust, which are narrating the Game Theory. Just after the inception of Pakistan, it was the instinct desire to have cordial relations with its neighbors, especially the Muslim world. Unfortunately, the misapprehension of Afghanistan created the vacuum of non-cooperation between the two Muslim neighboring countries. Afghanistan policy of defection over Durand Line, Pakhtunistan and support for the militants in FATA and Baluchistan and resultantly Pakistan’s role in Soviet invasion, support for Mujahedeen and Taliban, further aggravated the situation. Though limited cooperation was seen during Daud era, Taliban regime and in the War against Terrorism but it could not let cooperation to get roots. Furthermore, the mistrust and misunderstanding provided an opportunity to others to interfere in their affairs which acted as adding fuel to fire. The divested situation negatively affects both sides. So, the policy of cooperation and Nash-equilibrium is good payoff for both the countries. This paper employs the approach of Game Theory to analyses the payoff of cooperation and non-cooperation in the light of Pak-Afghan relations during Cold War. Furthermore, it investigates that how much the policy of cooperation and give-and-take will bring payoff for both of the two.